Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Solid acid catalyzed synthesis of furans from carbohydrates - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Reviews-Science and Engineering, 2016)
The alternative feedstock, biomass (particularly lignocelluloses), having the profuse availability, is promising for the synthesis of several value-added chemicals which are currently obtained from fossil feedstock. In this article, the synthesis of two extremely significant furan chemicals viz. furfural and 5-hydroxymethylfurfural (HMF) are discussed. In the synthesis of furans from biomass, numerous challenges, i.e., use of edible sugars as substrates, selectivity to furans, their isolation in pure form, reuse of catalyst, environmental issues, etc., are perceived and in the recent past researchers tried to resolve those by developing advance methodologies. This article comprehensively summarizes the latest progress made in the above-mentioned areas and also provides commentary on the analyses of results, rationale for observed activity and mechanisms, etc. It also discusses future aspects of this work.
Keywords: Biomass conversion; carbohydrates; cellulose; furans; furfural; hemicelluloses; HMF; solid acid catalyst

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-beta zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
The sulfonated H-beta zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) fromD-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N-2 physisorption, NH3-temperature programmed desorption and carbon-hydrogen-nitrogen-sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-beta (S-beta) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-beta catalyst at 160 degrees C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-beta; HMF; levulinic acid; sulfonated zeolite; yield

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield

Effect of furfural, acetic acid and 5-hydroxymethylfurfural on yeast growth and xylitol fermentation using Pichia stipitis NCIM 3497 - Bhavana, B. K.; Mudliar, Sandeep N.; Bokade, V. V.; Debnath, S. (Biomass Conversion and Biorefinery, 2024)
The valorization of C5 sugars (xylose) from hemicellulose of agro-industrial residues to xylitol, as one of the multi-products biorefinery approach, mandates the pretreatment of biomass which releases fermentable sugars along with the generation of biological inhibitors affecting xylitol fermentation. This study was therefore evaluated to understand the inhibitory kinetics of furfural, 5-hydroxymethylfurfural and acetic acid on xylitol fermentation. Xylitol fermentation was established using Pichia stipitis NCIM 3497 with xylose as a pure substrate optimized for xylitol yield and productivity of 0.48 g/g of xylose and 0.13 g/L/h, respectively. The functional relationship of yeast specific growth rate and limiting substrate (xylose) was expressed by Monod-type kinetics. The inhibition kinetics results indicated that the effect of inhibitors on xylitol fermentation was furfural > acetic acid > HMF. Furfural (500 mg/L) and acetic acid (1000 mg/L) reduced xylitol yield by 59% and 44%, respectively, with least reduction of 9.89% exhibited by HMF. The synergistic effect of 500 mg/L furfural, 500 mg/L HMF and 1000 mg/L acetic acid showed the highest reduction in xylitol yield of 67.6% as compared to the control. Kinetic studies predicted that the maximum concentration of furfural, HMF and acetic acid which inhibited P. stipitis growth was 884 mg/L, 3258 mg/L and 2922 mg/L, respectively, whereas xylitol production was completely inhibited at 1069 mg/L furfural, 3498 mg/L HMF and 3714 mg/L acetic acid. Furfural and acetic acid were found to be a competitive inhibitor, while uncompetitive inhibition was observed with HMF indicating negligible effect on xylitol fermentation.
Keywords: Acetic acid; furfural; HMF; Inhibition kinetics; Pichia stipitis; Xylitol fermentation